The effects of supplemental melatonin administration on the healing of bone defects in streptozotocin-induced diabetic rats - YILDIRIMTURK,Senem (2016)
ABSTRACT Diabetes mellitus (DM) causes an increased production of free radicals that can impair bone healing. Melatonin is a hormone secreted mainly by the pineal gland, which participates in the neutralization process of free radicals. Objective The aim of this study was to investigate histologic and biochemical effects of supplemental melatonin administration on bone healing and antioxidant defense mechanism in diabetic rats. Material and Methods Eighty-six Sprague-Dawley male rats were used in this study. Diabetes mellitus was induced by intraperitoneal (i.p.) administration of 65 mg/kg streptozotocin (STZ). Surgical bone defects were prepared in the tibia of each animal. Diabetic animals and those in control groups were treated either with daily melatonin (250 μg/animal/day/i.p.) diluted in ethanol, only ethanol, or sterile saline solution. Rats were humanely killed at the 10th and 30th postoperative days. Plasma levels of Advanced Oxidation Protein Products (AOPP), Malondialdehyde (MDA), and Superoxide Dismutase (SOD) were measured. The number of osteoblasts, blood vessels and the area of new mineralized tissue formation were calculated in histologic sections. Results At the 10th day, DM+MEL (rats receiving both STZ and melatonin) group had significantly higher number of osteoblasts and blood vessels as well as larger new mineralized tissue surfaces (p<0.05 for each) when compared with DM group. At the 30th day, DM group treated with melatonin had significantly lower levels of AOPP and MDA than those of DM group (p<0.05). Conclusion Melatonin administration in STZ induced diabetic rats reduced oxidative stress related biomarkers and showed beneficial effects on bone healing at short term.